It’s Five O’Clock Everywhere: A Framework for the Modernization of Time - Ryan Deal (Washington University Law Review, 2021)
This Note discusses existing legal procedures by which the current system of time could be modified to adapt to contemporary social changes and reduce time switching. Part I describes how the current system of timekeeping evolved and explains why it results in frequent time switching today. Part II considers the effectiveness of ongoing efforts by localities and states to avoid time switching by moving to a more favorable time zone. Part III evaluates attempts by state legislatures to minimize time switching by eliminating Daylight Saving Time (DST). Part IV briefly discusses the current international time zone scheme and contemporary contexts in which universal time is used on a global scale, suggesting that it offers a better model for a time-zone system in the United States. This Note ultimately argues in Part V that the United States should establish one permanent national time zone.
Keywords: Time zones; Time keeping; Daylight Saving Time; Universal time; National Time Zone